Bargaining and specialization in marriage - Murat Iyigun (Institute for the Study of Labor (IZA), 2005)
Can households make efficient choices? The fact that cohabitation and marriage are partnerships for joint production and consumption imply that their gains are highest when household members cooperate. At the same time, empirical findings suggest that spousal specialization and labor force attachment do influence the threat points of each spouse. As a consequence, specialization and spousal cooperation can be costly for household members. While the existing literature is divided on whether household choices are made efficiently or not, there does not yet exist an attempt to identify the marriage market and household dynamics that could induce endogenous cooperation and efficiency within the households. This paper incorporates the process of spousal matching into a household labor supply model in which (a) couples engage in home production, (b) there are potential gains from specialization but specializing in home production lowers market wages, and (c) intra-marital allocations are determined by an endogenous sharing rule that is driven by actual wage earnings. The incentives to specialize are high when wage or spousal endowment inequality is relatively high. Still, when there are equal numbers of men and women in the marriage markets, spousal specialization may not occur unless there exists a commitment mechanism. However, when the sex ratio is not equal to unity and there are singles in equilibrium who are of the same sex as spouses that specialize in market production, matching in asymmetric marriage markets induces spousal cooperation and specialization.
Keywords: C78; D61; D70; 330; collective model; marriage; household labor supply